Breast Feeding Practices in Urban Community of Surat City - Sunil Nayak; Jay Padodara; Sushil Patel; Vaibhav Gharat; Swati Patel; Vivek Choksi; Toral Desai (Medsci Publications, 2010)
The breast feeding practices adopted in terms of duration, frequency and exclusiveness of breast feeding and weaning have great impact on complete physical, mental and psycho-social development of the child.  The objective of conducting the study is to evaluate the breast feeding practices adopted by women in urban community, and s to study factors affecting time of initiation of breast feeding, age of weaning, and food given to the baby other than breast milk. The current cross sectional study conducted among 200 women reveal that 70% of mothers were able to start breast feeding within first hour of life after normal delivery. Out of 26 complicated deliveries, 6 mothers were able to start breast feeding within 4 hours of life. The major reasons for delay in starting of breast feeding were uneasiness to mother and not having adequate breast milk. Exclusive breast feeding was practiced by 50% of the mothers for first six month of life. The common reason given by mother for not giving exclusive breast feeding were no knowledge of exclusive breast feeding (40%) and not having adequate breast milk(35%). This study emphasizes the need of breast feeding education programme regarding the duration of exclusive breast feeding and the age of weaning.